Docetaxel-loaded magnetic nanostructured lipid carrier functionalized with fish oil-coated iron oxide nanoparticles intended for lung cancer treatment - Idris, Auni Hamimi (2021)
Lung cancer is currently the most prevalent cause of cancer mortality due to late diagnosis and lack of curative therapies. Docetaxel (Dtx) is clinically proven to be effective, but poor aqueous solubility and non-selective cytotoxicity limit its therapeutic efficacy. Increasing the bioavailability of Dtx while potentially monitoring the therapeutic response via Magnetic Resonance Imaging is an appropriate strategy for effective drug delivery. In this work, a nanostructured lipid carrier (NLC) loaded with iron oxide nanoparticles (IONP) and Dtx (Dtx- MNLC) was developed as a potential theranostic agent for lung cancer treatment. The IONP was synthesised from thermal decomposition of iron oxyhydroxide (Fe(O)OH) and functionalised with Menhaden fish oil (MFO). Its physicochemical properties, cytotoxicity, and potential as contrast agents were then evaluated. The NLC was optimised using Response Surface Methodology. The amount of IONP and Dtx loaded into the Dtx-MNLC was quantified using Inductively Coupled Plasma Optical Emission Spectroscopy and highperformance liquid chromatography. Dtx-MNLC was then subjected to assessment of physicochemical characteristics, in vitro drug release, and cytotoxicity. IONP having 10 nm size was synthesised at 60 minutes aging time and 400 rpm stirring rate. The MFO-coated IONP (MFO-IONP) showed excellent aqueous dispersibility and good negative contrast with transverse relaxation rate of 9.85 mM-1s-1. MFO-IONP exhibited dose-dependent toxicity with higher toxicity on human lung carcinoma cells (IC50= 41 μg/mL) than human lung fibroblast cells (IC50 = 494 μg/mL) within 72 hours exposure. The RSM model suggested the NLC formulated with 6% w/w lipid (MCT/ Precirol ATO 5) and 7.7% w/w emulsifier (TPGS/ Lipoid S75), with 20 minutes stirring time and 400 rpm stirring rate to achieve 187 nm particle size. Dtx loading percentage was determined at 3.98% w/w, and 0.36 mg/mL MFO-IONP was loaded into the Dtx- MNLC. The formulation showed a biphasic drug release in a simulated cancer cell environment, where 40% of Dtx was released for the first 6 hours, and 80% cumulative release was achieved after 48 hours. Dtx-MNLC exhibited higher cytotoxicity to A549 cells than MRC5 in a dose-dependent manner. Furthermore, the toxicity of Dtx-MNLC to MRC5 was lower compared to the commercial formulation. In conclusion, Dtx-MNLC shows the efficacy to inhibit lung cancer cells growth, yet reduced toxicity on healthy lung cells and potentially capable as a theranostic agent for lung cancer treatment.